(12x+6)(13x-1)=

Simple and best practice solution for (12x+6)(13x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x+6)(13x-1)= equation:


Simplifying
(12x + 6)(13x + -1) = 0

Reorder the terms:
(6 + 12x)(13x + -1) = 0

Reorder the terms:
(6 + 12x)(-1 + 13x) = 0

Multiply (6 + 12x) * (-1 + 13x)
(6(-1 + 13x) + 12x * (-1 + 13x)) = 0
((-1 * 6 + 13x * 6) + 12x * (-1 + 13x)) = 0
((-6 + 78x) + 12x * (-1 + 13x)) = 0
(-6 + 78x + (-1 * 12x + 13x * 12x)) = 0
(-6 + 78x + (-12x + 156x2)) = 0

Combine like terms: 78x + -12x = 66x
(-6 + 66x + 156x2) = 0

Solving
-6 + 66x + 156x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6'.
6(-1 + 11x + 26x2) = 0

Factor a trinomial.
6((-1 + -2x)(1 + -13x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5

Subproblem 2

Set the factor '(1 + -13x)' equal to zero and attempt to solve: Simplifying 1 + -13x = 0 Solving 1 + -13x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -13x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -13x = 0 + -1 -13x = 0 + -1 Combine like terms: 0 + -1 = -1 -13x = -1 Divide each side by '-13'. x = 0.07692307692 Simplifying x = 0.07692307692

Solution

x = {-0.5, 0.07692307692}

See similar equations:

| 7(x+5)-58=18 | | 2x+24=-8-4(2x-8) | | 5e=55 | | 5.9=-A-4.8 | | 2k+3-k=k+2 | | -9=1-6x+2 | | -10/2(-5)= | | 9r=-6 | | x+6=8x-15 | | 7-3x-10=-66 | | -1/6*b=3 | | 4k+3=10-3k | | -3(y+2)=-2(y+4)-y | | -3x^2=1 | | (19x+6)(20x)= | | 0=3x^2+1 | | 5m^2+13m+15=0 | | f(x)=5x^2+10x+1 | | x^3-5x^2-5x-1=0 | | 3y-9y+5w+w= | | c/4+3=8 | | 5-1k=21-3k+12 | | (51x+3)(1+52x)= | | X/8-6=8 | | 5+x/8=-3 | | (x+2x^3-3)/(x-1)=0 | | .5x+16(x+2)=48.5 | | 5x-11=10+12x | | (x+2x^3-3)/(x-1) | | x^4-9x^2-52=0 | | 3+y=19 | | 2z-3-2(1+z)=-5 |

Equations solver categories